Prevalencia del síndrome de ojo seco en pacientes diagnosticados de glaucoma que acuden al centro oftalmológico Visión Care - Ordóñez Albia, Christopher Daniel (2021)
Dry eye disease is a multifactorial tear deficiency disorder of the ocular surface which symptoms can considerably limit the performance of multiple activities related to visual function, mainly when it is secondary to another disease such as glaucoma. With the aim of relating these two diseases that progressively affect the local population, the present observational, cross-sectional study was proposed, and developed with a sample of 88 patients, diagnosed and treated for glaucoma at the Ophthalmological Center "Vision Care ”, between May 2019 and April 2020; obtaining the following results: among the 88 patients with glaucoma there exist a prevalence of 29,55% (n = 26 patients) according to the But test; furthermore, the most common symptoms in patients with suspected dry eye syndrome are dry eye, foreign body sensation, grit sensation, sensitivity to light, watery eyes and eye fatigue. Finally, from the patients diagnosed with dry eye syndrome, 57,69% (n = 15) were staged with a mild OSDI, 30,77% (n = 8), were staged with a moderate OSDI and 11,54% (n = 3) were staged with severe OSDI. Concluding that, there is indeed a prevalence of dry eye syndrome, mainly when it is in a mild and normal stage. Key Words: Glaucoma, dry eye, stage, symptoms.